The Term Structure of Interest Rates: Departures from Time-Separable Expected Utility - Allan W. Gregory; Graham M. Voss (Queen's University, Department of Economics, 1990)
This paper assesses the ability of general equilibrium models of asset pricing using two recently developed sets of preferences to quantitatively account for the observed variability in the Canadian term structure of interest rates. the preference structures are non-expected utility and habit persistence associated with Epstein and Zin (1989a) and Constantinides (1990) respectively. The framework adopted follows Backus, Gregory and Zin (1989) where a numerical version of the theory is specified and empirical features of the artificial economy are compared against actually data. Neither preference structure is able to satisfactorily mimic the magnitude or the variability of the risk premiums.
Keywords: 330